2010
DOI: 10.1016/j.juro.2010.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supports a Faster Growth Rate and/or Earlier Transformation to Clinically Significant Prostate Cancer in Black Than in White American Men, and Influences Racial Progression and Mortality Disparity

Abstract: Purpose The incidence of prostate cancer is approximately 60% higher and the mortality rate is 2 to 3 times greater in black than in white American men. We propose that a more rapid prostate cancer growth rate and/or earlier transformation from latent to aggressive prostate cancer in black than in white men contribute to this disparity. Materials and Methods We evaluated entirely embedded prostate glands on autopsy from 1,056 black and white men who died of causes other than prostate cancer. We also reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
203
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(229 citation statements)
references
References 23 publications
14
203
2
5
Order By: Relevance
“…The current hypothesis is that most aged men have prostate cancer, and they have cells in their prostates that if observed on a needle biopsy would be diagnosed as prostate cancer (58). This fact is supported by the study of Powell et al (59) showing that prostate carcinoma can be found in 50% of males 50 years of age, and 70-80% of men over the age of 70 years, dying from non-prostate cancer-related causes. These lesions are called 'microscopic' or 'latent' foci of prostate cancer, typical of their small size, non-progressiveness, clinically insignificance and rare detection through routine prostate cancer screening.…”
Section: Cancer Patients Healthy Controls ---------------------------mentioning
confidence: 81%
“…The current hypothesis is that most aged men have prostate cancer, and they have cells in their prostates that if observed on a needle biopsy would be diagnosed as prostate cancer (58). This fact is supported by the study of Powell et al (59) showing that prostate carcinoma can be found in 50% of males 50 years of age, and 70-80% of men over the age of 70 years, dying from non-prostate cancer-related causes. These lesions are called 'microscopic' or 'latent' foci of prostate cancer, typical of their small size, non-progressiveness, clinically insignificance and rare detection through routine prostate cancer screening.…”
Section: Cancer Patients Healthy Controls ---------------------------mentioning
confidence: 81%
“…Contrariwise the majority of patients in our study are symptomatic (95.8%) and presented with LUTS and features of locally advanced or metastatic disease. Numerous studies have found that black men have a higher stage of disease at presentation and are more likely to die of their prostate cancer than their white counterparts [15][16][17]. Powell [17] evidenced that African Americans have similar pathogenic mechanisms and age at PCa initiation to Caucasians but they have a faster growth rate and/or an earlier transformation to clinically significant PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that black men have a higher stage of disease at presentation and are more likely to die of their prostate cancer than their white counterparts [15][16][17]. Powell [17] evidenced that African Americans have similar pathogenic mechanisms and age at PCa initiation to Caucasians but they have a faster growth rate and/or an earlier transformation to clinically significant PCa. Late presentation of PCa is commonly reported from SSA [5,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer may be biologically more aggressive among Black men though controversial (7)(8)(9). In a study by Cross et al (10), even though African-American men presented at a younger age and with more advanced disease compared with White men with prostate cancer, PSA outcome after RP when controlled for known clinical predictive factors was not statistically different.…”
Section: Racementioning
confidence: 98%
“…Prostate cancer may be biologically more aggressive among Black men though controversial (7)(8)(9)(10)(11). The prevalence of prostate cancer in Brazil is higher in Black men compared to White men (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%